Effects of shrimp chitosan on the physical properties of handsheets - Khantayanuwong, Somwang; Khemarom, Chutatip; Salaemae, Sumaida (Agriculture and Natural Resources, 2017)
The effects of shrimp chitosan as an additive were determined on the physical properties of handsheets, especially: their brightness, opacity, surface roughness and surface water absorptiveness. Commercial, hardwood, bleached kraft pulp was beaten to attain 390 mL Canadian standard freeness and then made into four sets of handsheets by mixing each part of the beaten pulp slurry with shrimp-chitosan solution to obtain 0.00%, 0.25%, 0.50% and 0.75% (oven dry weight (o.d. wt.) of pulp), respectively, in accordance with standard test methods. All the sets of handsheets were conditioned for 1 wk and then tested for their mechanical and physical properties at 50 ± 2% relative humidity and 23 ± 1 oC. The results indicated that even though there were some substantial decreases in some physical properties of shrimp-chitosantreated handsheets (brightness, surface roughness and surface water absorptiveness), their opacity was slightly increased. Most of the mechanical properties of shrimp-chitosan-treated handsheets such as the bursting index, folding endurance, tensile index, modulus of elasticity and tensile energy absorption were greatly increased with the addition of shrimp chitosan at 0.25% o.d. wt. of pulp to 0.50% o.d. wt. of pulp. However, there was no effect on the tearing strength by adding shrimp chitosan to the handsheets.